Новая форма оленя из неогеновых отложений юга Украины - Короткевич, Е.Л. (Вестник зоологии, 1971)
In the quarry of the brick plant in the town of Ananiev (the Odessa region) the
jemains of a fossil deer were found at a depth of 8—12 m under the sand layer. Its horns
are restored and kept in the collection of the Paleontological museum of Odessa State
University. They are characterized by a comparatively small sizes, spade-like broadened
upper part of the stem, absence of the supraorbital and glacial processes, presence of tiltmedial process, located high above the burr in one plane with the horn stem and posterior
process (but considerably lower than the latter).
The above-mentioned peculiarities in the structure indicate its close relation to the
group of gigantic deers on the one hand, and on the other — the primitiveness and belonging (taking into account the time of existence) to the new genus and species —
Neomegaloceros gracilis gen et sp. п., the description of which is presented in the given
article.